2019
DOI: 10.1249/mss.0000000000001903
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Modeling High School Sport Concussion Symptom Resolve

Abstract: Introduction Concussion prevalence in sport is well recognized, so too is the challenge of clinical and return-to-play management for an injury with an inherent indeterminant time course of resolve. A clear, valid insight into the anticipated resolution time could assist in planning treatment intervention. Purpose This study implemented a supervised machine learning–based approach in modeling estimated symptom resolve time in high school athletes who in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Hence, a guideline-corresponding followup by AI algorithms after minutes to hours could be built into the app to enable a fast implementation from the recommendations [20]. Other studies have already shown significant differences in diagnostic capacities among different algorithms in the context of concussion [21], but data also suggested a great potential of AI diagnostic support as assisting tool to clinicians [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a guideline-corresponding followup by AI algorithms after minutes to hours could be built into the app to enable a fast implementation from the recommendations [20]. Other studies have already shown significant differences in diagnostic capacities among different algorithms in the context of concussion [21], but data also suggested a great potential of AI diagnostic support as assisting tool to clinicians [22].…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects must be critically discussed in the context of this report. One major limitation is that this case report only used one of various existing apps on the market, and the efficacy will likely vary between different algorithms [21]. In general, it has to be acknowledged that nowadays the purpose of AI-based chatbots cannot yet be seen as diagnosing complex clinical injuries or pathologies, instead is intended to give patients useful insight before getting a chance to meet or talk with a medical professional.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes included post-concussive symptoms (Bergeron et al, 2019;Cnossen et al, 2017), functional outcome (Gupta et al, 2017;Nishi et al, 2019;Walker et al, 2018), indicators of mood and psychological symptoms (Hirata et al, 2016;Huttunen et al, 2016;Shafiei et al, 2017), and employment (Stromberg et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For our preliminary analysis, we employed 10 commonly used learning algorithms: 5-Nearest Neighbors, two versions of C4.5 decision tree, Logistic Regression, Multilayer Perceptron, Naïve Bayes, two versions of Random Forest, Radial Basis Function Network, and Support Vector Machine. Key attributes and contrasts of these algorithms have been described elsewhere [21] (see respective Appendix). These were chosen because they represent a variety of different types of learners and because we have demonstrated success using them in previous analyses on similar data.…”
Section: Predictive Modelingmentioning
confidence: 99%